Weapons of opportunity : a novel [large type] - Brown, Dale, 1956- (Brown, Dale, 1956- Nick Flynn novel, 2023)
When a CIA executive goes dark, Nick Flynn must step in. Russian oligarch Pavel Voronin and his shadowy Raven Syndicate are back, supported by Russia's autocratic president. Voronin intends to unleash a force of advanced stealth aircraft against the US in order to make Moscow supreme and cement his own rise to power. With millions of lives at stake, Flynn and his team must track Voronin's operatives and mount a risky counterattack deep into hostile territory. If they fail, the consequences will be horrific.